How to become a leader in an emerging new global market: The determinants of French wine exports, 1848-1938 - María Isabel Ayuda; Hugo Ferrer-Pérez; Vicente Pinilla (European Historical Economics Society (EHES), 2018)
When studying the emergence of new global markets it is essential to consider how countries and companies compete to obtain advantageous positions. Our objective is to study how France obtained an initial leadership position in the new global wine market which it subsequently consolidated. We will also analyse the main determinants of its exporting success. In order to do this we have quantified its exports and examined its evolution and its principal export markets. We have also used a gravity model for both ordinary wine and high quality wine in order to establish the key variables that explain this evolution. The article highlights the great efforts made by the exporters to improve the quality of their products and increase their sales using modern marketing techniques. Our econometric results also show some significant differences between the determinants of exports for the two types of wine. However, the exports of both products suffered the strong impact of a series of major events, such as The First World War, the Russian Revolution, the Prohibition in the United States and the Great Depression. The case of wine shows that the collapse of the first globalisation was not the same for all types of product.
Keywords: F14; N53; N54; N70; Q17; 330; Globalisation waves; Wine trade; French wine exports